Parallel Backtracking Algorithm for Hamiltonian Path Search - Grondzak, Karol; Martincova, Penka (Communications - Scientific letters of the University of Zilina, 2009)
The speed of calculations is a common problem to tackle in many areas of scientific research and real life. This paper presents an implementation of a parallel backtracking algorithm. The performance of the proposed algorithm is demonstrated on the problem of Hamiltonian Path search. Obtained results exhibit significant improvement of the parallel algorithm over the sequential one. Different aspects of parallelization of backtracking algorithm are studied and presented.